Analisis Pengaruh Budaya Organisasi, Program Magang, Dan Pelatihan Online Terhadap Kesiapan Calon Tenaga Kerja : - Ana Suyanti; Didik Subiyanto; Kusuma Chandra Kirana (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to explain the influence of organizational culture, internship programs, and online training on the readiness of prospective workers. This research will be conducted at the Faculty of Economics, University of Sarjanawiyata Tamansiswa on students who follow the organization. This study is a quantitative study and primary data were taken using questionnaires in nonprobability sampling census on 35 respondents. The Data was collected through google Forms, then processed using multiple linear regression analysis. The results showed that culture has a significant effect on the readiness of prospective workers. As for the internship program and online training has no influence on the readiness of job candidates. The results of this study are expected to be able to prepare students to become prospective workers who are ready to plunge in the world of work.